Defisit Anggaran dan Implikasinya terhadap Perkembangan Ekonomi dan Kinerja Keuangan Kabupaten Tebo - Astuti Prihatiningsih; M. Rachmad R; Syamsuddin HM (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2013)
This study aims to 1) To analyze the determinants that will influence the budget deficit in Tebo district budget. 2) To analyze whether there is a correlation between the budget deficit with Tebo regency economic development. 3) To analyze whether there is a correlation between the financial performance of the budget deficit with Tebo regency. The method used in this study is a secondary data analysis methods. Based on the results of testing the model regression shows the value of the F-count is high at 12 130. With an alpha of 0.05 df1 = 3, DF2 = 4 obtained F-table at 6:59. so the F-count> F-table. this indicates that the independent variables are jointly significant effect on the dependent variable, so that personnel expenditure, capital expenditure and spending on goods and services during the period 2004-2011 are jointly significant effect on the budget deficit in Tebo regency. Each there is an increase of 1 billion budget deficit, it will cause a reduction in personnel expenses amounted to 4.52 billion Tebo regency. Any increased capital expenditure budget of 1 billion budget deficit will increase by 5.01 billion. Any increased budget allocation of goods and services amounted to 1 billion, the budget deficit will increase by 8.17 billion. the greatest influence on the budget deficit from the budget allocation of goods and services. The results of the analysis of the budget deficit relationship with economic development in Tebo regency during 2006-2010 showed that the budget deficit by using a simple Pearson correlation test has a relationship of -0.07986. These results illustrate that the budget deficit has a negative relationship with economic development. The results of the analysis of the relationship with the budget deficit in the region's financial performance during the period 2006-2010 Tebo regency showed that the budget deficit with the financial performance using tools Pearson correlation test has a relationship of -0.04703. The results illustrate that the budget deficit has a negative relationship with financial performance. Keywords: budget deficit, budget allocation, capital expenditure budget